Proximal Fibular Osteotomy for Knee Osteoarthritis: Short-Term Pain Relief or Long-Term Progression Prevention - Brajesh Dadarya; Mayank Pratap Singh; Mukesh Kumar Sharma; Tribhuwan Narayan Singh Gaur; Himanshy Rai; Tarun Singh Thakur (Journal of Pharmacy and Bioallied Sciences)
Objective: This study aimed to evaluate the long-term efficacy of proximal fibular osteotomy (PFO) in patients with medial compartment osteoarthritis (OA) of the knee, focusing on pain relief, functional outcomes, and radiological changes. Methods: Patients aged 60–69 years with moderate to severe symptomatic degenerative knee OA were included. The patients underwent PFO, and their outcomes were assessed at multiple time points (immediate postoperative, 3 weeks, 6 weeks, 3 months, 6 months, and 12 months). Pain was measured using the visual analogue scale (VAS), while knee function was assessed using the American Knee Society Score (KSS). Radiological parameters, including femorotibial and joint convergence angles, were measured preoperatively and postoperatively. Results: Significant improvements in both pain (VAS) and knee function (KSS) were observed over time. The mean VAS score decreased from 7.70 preoperatively to 1.57 at 12 months postoperatively. Similarly, the KSS increased from 33.1 preoperatively to 84.5 at 12 months. Radiologically, the femorotibial angle improved from 184.05° to 181.8° and the joint convergence angle improved from 3.13° to 1.3°. Physiotherapy and BMI were found to influence long-term outcomes, with male patients and those with normal BMI showing better results. Conclusion: Proximal fibular osteotomy is an effective, safe, and affordable surgical option for providing pain relief and improving function in patients with medial compartment knee OA. Regular physiotherapy and weight management play a crucial role in optimizing long-term outcome.